Incidental Gallbladder Cancer: A Clinicopathological Study. (11th September 2019) - Dhorajiya, Poojaben; Mannan, Rifat; Sharabi, Abdelsalam
Abstract: Objectives: Incidental gallbladder cancer (iGBC) is defined as gallbladder cancer (GBC) diagnosed at the time of or after cholecystectomy, performed for unsuspected benign gallbladder disease. Being rare, it is found in 0.2% to 2.9% cases of cholecystectomies performed for cholecystitis and represents approximately 40% of all GBCs. Here, we present the clinical and pathological features of iGBC diagnosed at our institute over a 10-year period. Methods: The pathology reports of GBC in patients who underwent simple cholecystectomies due to sole complain of cholecystitis between 2008 and 2018 were retrieved from electronic medical records. Cases with dysplasia (without invasive component), clinically suspected gallbladder malignancy, polyp (nonincidental), or cholecystectomies performed as a part of any other procedure were excluded. Results: Twenty-two cases of iGBC were diagnosed during the study period. Average patient age was 69.59 (range; 48-91) years, with a slight female (n = 12, 54.5%) predominance. Most common site was body (n = 7), followed by fundus (n = 4), neck (n = 2), and unknown (n = 9). Mean tumor size was 1.6 cm, where measurement of tumor size was possible (n = 16). Histopathological diagnoses were adenocarcinoma (n = 21) and carcinosarcoma (n = 1). The AJCC tumor staging was pT1a (n = 3), pT1b (n = 3), pT2 (n = 12), pT3 (n = 3), and unidentifiable (n = 1). Four cases were identified with N1 lymph node status. Cystic duct margin was positive in two cases. Perineural invasion was identified in three cases. Conclusion: iGBC after a cholecystectomy for clinically benign condition is a rare finding. Although cholecystitis is much more frequent in female, iGBC had only a slight predominance for female population in our study. It is more common in people over 60 years of the age, which is comparable to the literature. This entity still remains a diagnostic and therapeutic challenge, and management is often more complicated in cases with advanced stage.